Meningkatkan Kemampuan Mengenal Konsep Bilangan 1-10 melalui Media Game Edukasi Marbel Angka bagi Siswa Disabilitas Intelektual Ringan - Putri, Gusti; Taufan, Johandri; Damri, Damri; Handayani, Endang (Universitas Syiah Kuala, 2025)
This research is motivated by the low ability of students with mild intellectual disabilities in recognizing the concept of numbers 1-10. Students are only able to recognize number symbols without understanding the quantitative meaning and have difficulty in ordering numbers correctly. The purpose of this study is to improve the ability to recognize the concept of numbers 1-10 through the use of educational game media Marbel Angka for students with mild intellectual disabilities at SLB Negeri Ujung Ladang Kerinci. This study uses the Classroom Action Research (CAR) approach model Kemmis and McTaggart which includes four stages: planning, implementation of action, observation, and reflection. The research subjects consisted of four students of class III C with mild intellectual disabilities (two boys and two girls). Data collection techniques include observation, learning outcome tests, and documentation. Data analysis was carried out descriptively comparatively by comparing the results of the pre-cycle, cycle I, and cycle II. The results showed that the use of Marbel Angka media effectively improved the ability to recognize numbers 1-10. The average student score increased from 39% in the pre-cycle to 63% in cycle I, and reached 94% in cycle II. Students showed increased enthusiasm, participation, and independence during learning. Thus, the Marbel Angka educational game has been proven to be able to help students with mild intellectual disabilities understand number concepts in a more interesting and interactive way.